(untitled) (LACCEI, 2024)
Seaweeds are a rich source of components such as fiber, protein, minerals, vitamins, antioxidants and polyunsaturated fatty acids. They are low in calories and can help alleviate some of the nutritional and health problems associated with protein deficiency. The bioavailability of the Peruvian "yuyo" Chondracantus chamissoi provided the necessary support for this study to gain a better understanding of the nutritional value of the macroalga "yuyo" in its dehydrated state and its transformation into edible flour. The study was carried out using 20 kg of fresh macroalgae, packed in bags of 2 kg each, randomly taking samples of 150 and 90 g, which were vacuum-packed and stored frozen for later study. The analysis of the protein content of the dehydrated macroalgae Chondracanthus chamissoi showed that the higher the drying process, the higher the protein content in the same period of time, so that the protein content was inversely proportional to the dehydration temperature. In our study, the following results were obtained: at 40°C the protein content was 17.70% and at 60°C it was 18.20%. The protein content of dried Chondracanthus chamissoi at different temperatures was not the same as when fresh. The drying kinetics of the tests developed showed a direct relationship between temperature and dehydration rate